Who should take the Credit for the Bible Translation Works carried out in Eritrea? - W. Andemariam, Senai (Aethiopica, 2013)
The labour and sacrifices of the members of the Swedish Evangelical Mission and their predecessors in the production of scriptural works in Eritrea, and partly in Ethiopia, are praiseworthy. More acclaim is owed to these workers for their educating and/or involving native workers in the arduous task that often spanned two or three generations. When it comes to taking credit for these works, however, the native workers were rarely mentioned or, if they are mentioned, their contributions were not given the deserved recognition. This article attempts to highlight the remarkable contributions of native workers in the translation, or completion of the translation, of the Bible into four languages in Eritrea in contradistinction with the often exaggerated contributions of foreign missionaries in that successful mission.